Afghanistan rising - Ahmed, Faiz, 1980- (Cambridge, Massachusetts)
xiii, 430 sayfa
Keywords: “Challenging conventional narratives of Afghanistan as a perennial war zone and the rule of law as a secular-liberal monopoly, this book presents an account of the first Muslim-majority country to gain independence, codify its own laws, and ratify a constitution after the fall of the Ottoman Empire. Afghanistan Rising illustrates how turn-of-the-century Kabul, far from being a land-locked wilderness or remote frontier, became a virtual seaport for itinerant scholars and statesmen shuttling between Ottoman and British imperial domains. Tracing the country's longstanding but often ignored scholarly and educational ties to the metropolises of Istanbul, Damascus, and Baghdad, as well as greater Delhi and Lahore, the author explains how the court of Kabul became a contested space for diverse visions of modern Muslim reform at the turn of the twentieth century. Drawing on declassified records and manuscripts in Ottoman Turkish, Afghan Persian, Arabic, Urdu, and French, Afghanistan Rising presents a rare window into Afghanistan's legal heritage during a formative period in the country's history“--